AB0449 PAIN REDUCTION IN PATIENTS WITH RHEUMATOID ARTHRITIS RECEIVING TOFACITINIB MONOTHERAPY WITH OR WITHOUT PAIN MEDICATION: A POST HOC ANALYSIS OF POOLED DATA FROM PHASE 2, PHASE 3 AND PHASE 3B/4 STUDIES. (June 2019) - Taylor, Peter C.; Laar, Mart van de; Curtis, Jeffrey R.; Azevedo, Valderilio F.; Rivas, Jose Luis; Dahl, Palle; Wang, Lisy; Iikuni, Noriko; Shi, Harry; Woolcott, John; Benkhalifa, Salim; Gomez-Reino, Juan Jose; et al.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Pain is the most common symptom reported by patients (pts) with RA, 1, 2 thus reduction of pain is an important treatment goal. Objectives: To evaluate the effect of tofacitinib monotherapy ± pain medication on pain in pts with RA. Methods: This pooled post hoc analysis included pts who received tofacitinib 5 mg BID monotherapy (ie without csDMARDs) in Phase (P)2 (NCT00550446 ), P3 (ORAL Solo; NCT00814307 ) and P3b/4 (ORAL Strategy; NCT02187055 ) studies. Pts were stratified by concomitant use of 'any pain therapy' (opioids, plain analgesics [eg acetaminophen], NSAIDs or glucocorticoids [GC; ≤10 mg of prednisone or equivalent per day]), 'pure analgesics' (opioids or plain analgesics) and 'adjuvant analgesics' (NSAIDs or GC). Pts receiving pain medication at baseline (BL) maintained a stable dose during the studies; opioid and/or acetaminophen dose could be increased as rescue therapy. Efficacy outcomes were assessed at Month (M)3 and M6: change from BL (δ) in Pt Assessment of Pain (Pain; visual analogue scale [VAS]) and δPain stratified by DAS28-4(ESR)-defined low disease activity (LDA; ≤3.2) status at M3 and M6. Results: Of 676 pts who received tofacitinib 5 mg BID monotherapy, 604 (89%) received 'any pain therapy', 141 (21%) received 'pure analgesics' and 589 (87%) received 'adjuvant analgesics'. Demographics and BL disease characteristics, including disease activity and Pain VAS, were generally similar when stratified by use/type of pain medication. Reductions in pain (δPain VAS) at M3 and M6 were generally similar for pts who received tofacitinib with 'any pain therapy' vs those who did not receive 'any pain therapy' (Figure 1a ). There was a trend for a numerically greater reduction in pain at M3 and M6 in pts who received tofacitinib with 'any pain therapy' and who achieved LDA at M3 and M6 vs those who received tofacitinib with 'any pain therapy' and did not achieve LDA (95% CI overlapped; Figure 1b ). By contrast, pain reductions were similar for pts who received tofacitinib without 'any pain therapy', irrespective of LDA status. Similar trends were seen when pts were stratified by use of 'pure analgesics' and 'adjuvant analgesics' (data not shown). Conclusion: In this pooled post hoc analysis, pain reduction was similar in pts with RA receiving tofacitinib, regardless of pain medication use. Pain reduction was similar in pts receiving tofacitinib without 'any pain therapy', irrespective of LDA status. These results should be interpreted with caution, as pain medication could be used as rescue therapy, few pts received tofacitinib without 'any pain therapy', and confounding by indication cannot be excluded. Further analyses are required to explore the impact of tofacitinib on the relationship between reductions in pain and disease activity. References: [1] Walsh DA, McWilliams DF. Curr Pain Headache Rep 2012; 16: 509-17. [2] American College of Rheumatology Pain Management Task Force. Arthritis Care Res (Hoboken) 2010; 62: 590-9. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Sarah Piggott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc, Mart van de Laar Grant/research support from: AbbVie, Eli Lilly, Janssen-Cilag, Merck Inc, Pfizer Inc, Sanofi Genzyme, Speakers bureau: Eli Lilly, Pfizer Inc, Jeffrey R. Curtis Grant/research support from: Abbvie, Amgen, BMS, Corrona, Janssen, Lilly, Myriad, Pfizer, Roche/Genentech, UCB, Crescendo Bioscience Inc., Consultant for: Abbvie, Amgen, BMS, Corrona, Janssen, Lilly, Myriad, Pfizer, Roche/Genentech, UCB, Crescendo Bioscience Inc., Valderilio F Azevedo Grant/research support from: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Jose Luis Rivas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Palle Dahl Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Noriko Iikuni Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Harry Shi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Salim Benkhalifa Shareholder of: Pfizer SAS, Employee of: Pfizer SAS, Juan Jose Gomez-Reino Grant/research support from: Biogen, Gilead, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, Consultant for: Biogen, Gilead, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, maxime dougados Grant/research support from: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma